Indirect touch manipulation for interaction with stereoscopic displays - Simeone, Adalberto L. (2016 IEEE Symposium on 3D User Interfaces (3DUI), 2016)
Research on 3D interaction has explored the application of multi-touch technologies to 3D stereoscopic displays. However, the ability to perceive 3D objects at different depths (in front or behind the screen surface) conflicts with the necessity of expressing inputs on the screen surface. Touching the screen increases the risk of causing the vergence-accommodation conflict which can lead to the loss of the stereoscopic effect or cause discomfort. In this work, we present two studies evaluating a novel approach based on the concept of indirect touch interaction via an external multi-touch device. We compare indirect touch techniques to two state-of-the-art 3D interaction techniques: DS3 and the Triangle Cursor. The first study offers a quantitative and qualitative study of direct and indirect interaction on a 4 DOF docking task. The second presents a follow-up experiment focusing on a 6 DOF docking task. Results show that indirect touch interaction techniques provide a more comfortable viewing experience than both techniques. It also shows that there are no drawbacks when switching to indirect touch, as their performances in terms of net manipulation times are comparable.